Virtual power plant load aggregation optimization scheduling strategy for port adjustable resources - Zhang, Yun; Pan, Jie; Jiang, Shuiming; Zhu, Hui; Chen, Feng; Shu, Quanyan; Zhao, Jian (Frontiers in Energy Research, 2025)
In order to respond to the call of double carbon and further follow up the port energy construction in the new era, a virtual power plant load aggregation optimization scheduling strategy for port adjustable resources was proposed in view of the uncertainty of port adjustable resources and the insufficient consumption of new energy. Firstly, a port multi-energy coupling virtual power plant model including electricity, cold, heat and gas is constructed. Secondly, according to the load response law and demand characteristics, the load model of ship power change and electric heavy truck is added. Finally, considering the stepped carbon trading mechanism, the carbon emission cost of buildings is optimized by adjusting energy output, the carbon emission of buildings is improved, the clean transformation of energy structure is promoted, and the economic and environmental benefits of system operation are optimized. Through the comparative analysis of three scenarios, the introduction of flexible load and carbon trading mechanism in the energy system of intelligent buildings can give full play to the interaction and plasticity of the energy structure of intelligent buildings, effectively promote the consumption of clean energy, and realize the low-carbon economic operation of the energy system.